2019
DOI: 10.1093/mnras/stz510
|View full text |Cite
|
Sign up to set email alerts
|

Strong lensing reveals jets in a sub-microJy radio-quiet quasar

Abstract: We present e-MERLIN and EVN observations which reveal unambiguous jet activity within radio quiet quasar HS 0810+2554. With an intrinsic flux density of 880 nJy, this is the faintest radio source ever imaged. The findings present new evidence against the idea that radio loud and radio quiet quasars are powered by different underlying radio emission mechanisms, showing instead that the same AGN mechanism can operate as the dominant source of radio emission even in the very lowest radio luminosity quasars. Thank… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 118 publications
4
44
0
Order By: Relevance
“…The mm-continuum emission also shows a new feature labelled X near image B that is not present in the optical image. Component X also does not align with any of the radio components resolved in the e-MERLIN observations at 4.32 and 5.12 GHz of HS 0810+2554 (Hartley et al 2019).…”
Section: A Na Ly S I S O F T H E M M -C O N T I N U U M E M I S S I O N O F H S 0 8 1 0 +2 5 5mentioning
confidence: 76%
See 1 more Smart Citation
“…The mm-continuum emission also shows a new feature labelled X near image B that is not present in the optical image. Component X also does not align with any of the radio components resolved in the e-MERLIN observations at 4.32 and 5.12 GHz of HS 0810+2554 (Hartley et al 2019).…”
Section: A Na Ly S I S O F T H E M M -C O N T I N U U M E M I S S I O N O F H S 0 8 1 0 +2 5 5mentioning
confidence: 76%
“…More recently, Hartley et al (2019) using e-MERLIN and European VLBI Network observations have identified jet activity in HS 0810+2554. Specifically, their source reconstruction of the radio and HST data of HS 0810+2554 shows two jet components linearly aligned on opposing sides of the optical quasar core.…”
mentioning
confidence: 99%
“…It is possible that radio jets (typically associated with 'radio-loud' quasars) are being launched (e.g. Hartley et al 2019) but they are too small to be resolved in our radio images. Supporting this, earlier in the Symposium we were shown images of small jets in 'radio-silent' Seyfert galaxies (Lähteenmäki et al 2018), which are believed to be low-redshift analogues of quasars.…”
Section: What Accretion-related Mechanism Is Present?mentioning
confidence: 99%
“…2). Indeed, the relatively few available studies of RQ AGN at high and low resolution (e.g., Kellermann et al 1989Kellermann et al , 1994; Barvainis et al 1996;Kukula et al 1998;Ulvestad et al 2005;Leipski et al 2006;Padovani et al 2011;Doi et al 2011;Zakamska et al 2016a,b;Hartley et al 2019) have generally led to mixed results. This is not surprising, as all RQ AGN are powered by a SMBH and emit X-rays (from a corona), most are in star-forming hosts, and many display outflows.…”
Section: Introductionmentioning
confidence: 99%